2019
DOI: 10.1111/cas.14168
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib induces 3‐hydroxybutyric acid production in the liver of mice by peroxisome proliferator‐activated receptor α activation to aid its antitumor effect

Abstract: Apatinib, an antiangiogenic agent, shows efficient antitumor activity in a broad range of malignancies. Considering tumor is a type of metabolic disease, we investigated the metabolomics changes in serum and tumor after apatinib treatment and the molecular mechanism of characteristic changes associated with its antitumor efficacy. Molecules in serum and tumor tissue were extracted and analyzed by a gas chromatography‐mass spectrometry metabolic platform. Apatinib significantly inhibited e tumor growth and alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
(103 reference statements)
0
14
0
Order By: Relevance
“…Several studies have elucidated the antitumor effect of PPARA in various cancers, including breast cancer, prostate cancer, and ovarian cancer [ 32 34 ]. Some studies have drawn contradictory conclusions, suggesting that prolonged administration of PPARA agonists might cause hepatocarcinogenesis; however, the detailed mechanism remains unclear [ 35 ]. In the present study, we analyzed the expression levels of PPARs in pancancers and noted that PPARA was expressed at low levels in several types of tumors, including colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have elucidated the antitumor effect of PPARA in various cancers, including breast cancer, prostate cancer, and ovarian cancer [ 32 34 ]. Some studies have drawn contradictory conclusions, suggesting that prolonged administration of PPARA agonists might cause hepatocarcinogenesis; however, the detailed mechanism remains unclear [ 35 ]. In the present study, we analyzed the expression levels of PPARs in pancancers and noted that PPARA was expressed at low levels in several types of tumors, including colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the result of non-alcoholic fatty liver disease (NAFLD) patients with steatosis ( Rodríguez-Gallego et al, 2015 ). Feng et al (2019) has shown a similar result that the activation of peroxisome proliferator-activated receptor α (PPAR α) in the liver can promote the utilization of fatty acids and increase the content of 3-hydroxybutyric acid in serum. Therefore, the above results indicate the decrease of fatty acid β oxidation in FLHS laying hens.…”
Section: Discussionmentioning
confidence: 87%
“…There is interplay between VEGF (A, B, C, D, and E) ligands and VEGF receptors (VEGFR-1, 2, and 3) ( Colombo et al, 2018 ). Activation of VEGFR, a member of the receptor tyrosine kinase (RTK) family, will then lead to upregulation of multiple cellular pathways (PI3K/AKT) that promote cell growth and angiogenesis ( Feng et al, 2019 ; Wu et al, 2019 ; Kaufman et al, 2021 ). Transforming growth factor-β1 (TGF-β1) is a polypeptide growth factor that can activate the PI3K/Akt signaling pathway by binding to TβR-I and TβR-II on fibroblasts and other cell membranes and activating receptors ( Li et al, 2012 ; Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%